The New Fugacity Calculation in Finite Nuclear Matter - Rizal Kurniadi; Abdul Waris (Indonesian Journal of Physics, 2007)
The caloric curve of hot nuclei in equilibrium states have been calculated with a new prescription namely a new fugacity calculation. In this technique, the fugacity is directly proportional to the nucleon density; hence, the fugacity is obtained through thermal wavelength. In contrast with the constant fugacity, the choosing of thermal wavelength approximation gives a simpler way to calculate the density profile and the entropy of finite nuclear matter. Variation of thermal wavelength value does not affect to the density and entropy. The phase transition temperature is dependent concerning both of the thermal wavelength value and the potential deep.